A stable bidentate protein binder achieved via DNA self-assembly driven ligand migration1. Issue 71 (14th September 2015) - Su, Xiaoye; Zhou, Xiao; Zhang, Nan; Zhu, Mengyuan; Zhang, Hong; Jayawickramarajah, Janarthanan
<x xml:space="preserve">Abstract</x> DNA-templated ligand migration, involving the transfer of a binding head-group, leads to the conversion of a low-affinity human serum albumin binder (1) to a high affinity bidentate binder (2). Further, the activated binder remains effective despite denaturation (3) and degradation (4).